Investigation of gating parameter, temperature and density effects on mold filling in the lost foam casting (LFC) process by direct observation method - Sharifi, A.; Mansouri Hasan Abadi, M. (Metallurgical and Materials Engineering, 2013)
Mold filling sequence of A356 aluminum alloy was investigated with the aid of direct observation method (photography method). The results show that increase of the foam density causes decrease of the filling rate and increase of the filling time. Foam density has more pronounced effect on mold filling rate rather than pouring temperature. Gating design also affects the profile of molten metal advancement in the mold. The results show that the higher filling rate was obtained with G2 gating than with other gating system. Regarding the mold filling pattern, G3 gating system has more effective contact interface than G2 gating system and has lower filling time. Filling time in G4 gating and G1 gating system are nearly the same.